Clinical and histological determinants of nonalcoholic steatohepatitis and advanced fibrosis in elderly patients. Issue 5 (2nd October 2013) - Noureddin, Mazen; Yates, Katherine P.; Vaughn, Ivana A.; Neuschwander‐Tetri, Brent A.; Sanyal, Arun J.; McCullough, Arthur; Merriman, Raphael; Hameed, Bilal; Doo, Edward; Kleiner, David E.; Behling, Cynthia; Loomba, Rohit; et al.
<x xml:space="preserve">Abstract</x> The characteristics of nonalcoholic fatty liver disease (NAFLD) in elderly patients are unknown. Therefore, we aimed to examine the differences between elderly and nonelderly patients with NAFLD and to identify determinants of nonalcoholic steatohepatitis (NASH) and advanced fibrosis (bridging fibrosis or cirrhosis) in elderly patients. This is a cross‐sectional analysis of adult participants who were prospectively enrolled in the NASH Clinical Research Network studies. Participants were included based on availability of the centrally reviewed liver histology data within 1 year of enrollment, resulting in 61 elderly (age ≥65 years) and 735 nonelderly (18‐64 years) participants. The main outcomes were the presence of NASH and advanced fibrosis. Compared to nonelderly patients with NAFLD, elderly patients had a higher prevalence of NASH (56% versus 72%, P = 0.02), and advanced fibrosis (25% versus 44%, P = 0.002). Compared to nonelderly patients with NASH, elderly patients with NASH had higher rates of advanced fibrosis (35% versus 52%, P = 0.03), as well as other features of severe liver disease including the presence of ballooning degeneration, acidophil bodies, megamitochondria, and Mallory‐Denk bodies (P ≤ 0.05 for each). In multiple logistic regression analyses, independent determinants of NASH in elderly patients included higher aspartate aminotransferase (AST) (odds ratio [OR] = 1.12, P = 0.007) and lower platelets (OR = 0.98, P = 0.02); and independent determinants of advanced fibrosis included higher AST (OR = 1.08, P = 0.007), lower alanine aminotransferase value (OR = 0.91, P = 0.002), and an increased odds of having low high‐density lipoprotein (OR = 8.35, P = 0.02). Conclusion: Elderly patients are more likely to have NASH and advanced fibrosis than nonelderly patients with NAFLD. Liver biopsy may be considered in elderly patients and treatment should be initiated in those with NASH and advanced fibrosis. (HEPATOLOGY 2013;58:1644–1654)